IMPROVING SPEAKING SKILL THROUGH PROBLEM SOLVING APPROACH - Nenti Siti Asih; Wikanengsih Wikanengsih (IKIP Siliwangi, 2018)
Speaking skills in classroom are considered as the most difficult skills performed by students. This is justified by the value of Bahasa Indonesia subject that is still low or below KKM (Minimum Completion Criteria), especially in speaking skills. Hence, there needs to be an effort to improve the speaking skill in learning Bahasa Indonesia. One of them is by using problem solving approach. Because problem solving is an approach based on reflective or logical and critical thinking processes. The purpose of this study is to identify differences in student learning outcomes before and after using the problem solving approach. The research method used is quasi-experimental method. The sample in this research is the 8th grade students in one of the private junior high school in Kabupaten Bandung which amounted to 35 people. Based on the result of the research, Sig. (1-tailed) 0,003 < 0.05 so it means the ability of knowledge of students' speaking skills learning using problem solving approach is better than the learning using the usual approach. The significance level is at 0.05. And the problem solving approach is appropriately applied in the learning of Bahasa Indonesia.